Navigating cybersecurity challenges: Legal implications and organizational strategies (International Seven Journal of Multidisciplinary, 2024)
The increasing frequency and sophistication of cybersecurity incidents—such as data breaches, ransomware attacks, and system violations—highlight significant legal and organizational challenges. Despite rising investments in cybersecurity, these incidents continue to evolve, presenting complex issues for both corporations and regulators. Traditional legal frameworks, primarily focused on financial damages, fail to address non-financial harms like emotional and psychological impacts on consumers. Studies by Teichmann and Wittmann (2022) and Kilovaty (2021) reveal gaps in current cybersecurity laws, emphasizing the need to incorporate psychological damages and enhance corporate liability standards. Research by Frank, Grenier, and Pyzoha (2021) demonstrates the increasing litigation risks for boards of directors following cybersecurity incidents. Their findings suggest that prior cyberattacks raise the likelihood of being held liable, though implementing frameworks like the American Institute of Certified Public Accountants’ (AICPA) risk management guidelines can mitigate these risks. Additionally, Eijkelenboom and Nieuwesteeg (2020) analyze the disclosure of cybersecurity information in Dutch annual reports, finding a lack of transparency despite legal requirements. Their study underscores the need for better self-regulation or potential legal mandates to improve cybersecurity reporting. Falowo et al. (2022) examine the impact of digital interconnectedness on cybersecurity risks, noting that malware and phishing attacks are prevalent. Their research highlights the importance of organizational preparedness and adherence to frameworks such as the National Institute of Standards and Technology (NIST) guidelines for effective incident response. Sen (2018) identifies ongoing technical, economic, legal, and behavioral challenges that hinder effective cybersecurity, advocating for new strategies to overcome these barriers. Overall, enhancing cybersecurity resilience requires a comprehensive approach, integrating improved legal frameworks, organizational transparency, and proactive risk management.